Production of biodiesel from palm oil using chemically treated fish bone catalyst - Sulaiman, Sarina; Shah, Beenish; Jamal, Parveen (AIDIC, 2017)
The waste food material namely fish bone is screened for biodiesel synthesis by transesterification reaction to achieve the highest biodiesel yield. The fish bone was chemically treated with Al(NO3)3.9H2O to enhance the biodiesel yield. The solid oxide materials were calcined at 900 °C for 2 - 4 h to convert CaCO3 to CaO species. Transesterification was carried out at 65 °C for 4 h with 12 : 1 methanol to oil ratio. The experiment was designed by central composite design with 23 factorial and three centre points to determine the optimum CaO (calcined fish bone) loading, calcination time for catalyst and amount of chemically treated fish bone, wt%. The highest yield of 94.30 wt% was achieved at optimal conditions of calcination time (6.11 h), catalyst loading wt% of (4.02 wt%) and CaO (calcined fish bone) loading of (34.49 %).